Respostas
respondido por:
1
x - 3y = 1
2x + 5y = 13
x = 1 + 3y
2( 1 + 3y) + 5y = 13
2 + 6y + 5y = 13
2 + 11y = 13
11y = 13 - 2
11y = 11
y = 11/11
y = 1
substituição :
x = 1 + 3y
x = 1 + 3 . 1
x = 1 + 3
x = 4
prova real :
x - 3y = 1
4 - 3 . 1 = 1
4 - 3 = 1
1 = 1 : correto
2x + 5y = 13
2(4) + 5(1) = 13
8 + 5 = 13
13 = 13 : correto
2x + 5y = 13
x = 1 + 3y
2( 1 + 3y) + 5y = 13
2 + 6y + 5y = 13
2 + 11y = 13
11y = 13 - 2
11y = 11
y = 11/11
y = 1
substituição :
x = 1 + 3y
x = 1 + 3 . 1
x = 1 + 3
x = 4
prova real :
x - 3y = 1
4 - 3 . 1 = 1
4 - 3 = 1
1 = 1 : correto
2x + 5y = 13
2(4) + 5(1) = 13
8 + 5 = 13
13 = 13 : correto
jjjjjjj:
Muito Obrigada voce me ajudou muito
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás